Mining ultrahigh-strength sprayed concrete active admixture and preparation method thereof

By preparing an active admixture for ultra-high strength shotcrete used in mining, the problems of insufficient early strength, high transportation costs, and low bonding strength in coal mine roadway support have been solved. It achieves rapid hardening, low rebound rate, and high adhesion, promotes solid waste utilization, and improves construction efficiency and safety.

CN121107761APending Publication Date: 2025-12-12NANJING INST GENERAL INST OF COAL SCI +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511262873.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-05
Publication Date
2025-12-12

AI Technical Summary

Technical Problem

Existing shotcrete in coal mine roadway support suffers from problems such as slow early strength development, excessive use of cement and silica fume leading to increased transportation costs, excessive rigidity causing easy peeling, and insufficient bond strength.

Method used

Using secondary aluminum ash, coal gangue, and calcium oxide as the main raw materials, and through specific proportions and processes, an active admixture for ultra-high strength shotcrete in mining is prepared. Combined with a composite activator and nano-calcium carbonate, the particle size distribution and early activation are optimized to form a shotcrete material with high strength and good adhesion.

Benefits of technology

It achieves rapid hardening performance (compressive strength ≥20MPa in 2 hours), low rebound rate (≤5%) and high bond strength (≥2.5MPa), reducing material costs and transportation expenses, improving construction efficiency and safety, and promoting the utilization of solid waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121107761A_ABST
    Figure CN121107761A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of new materials for coal mine tunnel construction, in particular to a mining ultrahigh-strength sprayed concrete active admixture and a preparation method of the mining ultrahigh-strength sprayed concrete active admixture. The prepared UHPC has excellent jet constructability, rapid hardening performance and long-term durability, realizes nearby high-valued utilization of coal mine solid waste, solves the problems of low strength, high rebound rate and long maintenance period of a traditional roadway spraying material, can replace traditional guniting concrete to be used for rapid support construction and repair of a coal mine roadway, and has a wide application prospect. And the method has remarkable technical economic benefits and social benefits.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of new material preparation for coal mine roadway construction, in particular to a mine ultra-high strength shotcrete active admixture and a preparation method thereof. BACKGROUND

[0002] Traditional shotcrete is widely used in coal mine roadway support, mainly because it has three core advantages of rapid closure of surrounding rock, enhancement of overall stability, convenient and efficient construction, and mature technology and controllable cost, becoming a basic means of coal mine roadway support.

[0003] However, the existing technology mainly has the following defects: first, the existing technology mainly has the following defects; second, the early strength development is slow, which cannot meet the rapid support demand of the roadway; third, the total amount of cement and silica fume is more than 800 kg / m 3 , and the transportation cost in the coal mine area increases by more than 30%; fourth, the rigidity is too large to cause peeling due to the deformation of the surrounding rock, and the bonding strength is mostly less than 1.5 MPa. SUMMARY

[0004] The present application relates to the field of new material preparation for coal mine roadway construction, in particular to a mine ultra-high strength shotcrete active admixture and a preparation method thereof. 3 The present application relates to the field of new material preparation for coal mine roadway construction, in particular to a mine ultra-high strength shotcrete active admixture and a preparation method thereof.

[0005] To achieve the above-mentioned purpose, the present application provides a mine ultra-high strength shotcrete active admixture, which is prepared from the following raw materials in mass percentage: 30-45% of secondary aluminum ash, 25-40% of coal gangue, 15-25% of calcium oxide and 3-6% of composite activator; the composite activator is a mixture of sodium sulfate, calcium fluoride and sodium aluminate, and the mass ratio of the three is (2-3):1:(0.5-1); the coal gangue is underground tunneling or washing gangue with Al2O3 content ≥15% and carbon content ≤8%, and the particle size of 0.045-0.075 mm accounts for ≥40% after pretreatment.

[0006] The present application also provides a mine ultra-high strength shotcrete active admixture preparation method, which comprises the following steps:

[0007] Step S1: the pretreated secondary aluminum ash, coal gangue, calcium oxide and composite activator are weighed according to the proportion, put into a ball mill and dry mixed for 20-25 minutes, and the bulk density of the mixed powder is controlled to be 1.2-1.4 g / cm 3 ;

[0008] Step S2: Put the mixed powder into a rotary kiln, and protect it with inert gas. Increase the temperature to 850-950℃ at a rate of 5℃ / min, and keep the temperature for 2-4 hours to form a product with specific activity.

[0009] Step S3: After calcining the product and cooling it to below 100℃, carry out two-stage grinding to obtain a mine ultra-high strength shotcrete active admixture.

[0010] In step S1, the pretreatment of secondary aluminum ash is to soak the secondary aluminum ash in a 10%-15% hydrochloric acid solution for 2-4 hours, with a solid-liquid ratio of 1:5. After filtration, wash it with deionized water until it is neutral, and dry it at 105℃±5℃ until the weight is constant. Crush it and pass it through a 120-mesh sieve, with a particle size of 0.02-0.045mm accounting for ≥50%.

[0011] In step S1, the coal gangue is high-carbon coal gangue and low-carbon coal gangue, and the carbon content of the high-carbon coal gangue is 5%-8%, and the carbon content of the low-carbon coal gangue is ≤5%.

[0012] In step S1, the classification pretreatment of coal gangue is that the high-carbon coal gangue is calcined in two stages, first at 300-400℃ in air for 1 hour, then heated to 600℃±20℃ for 2 hours. The low-carbon coal gangue is directly calcined at 600℃±20℃ for 2 hours. After calcination, crush and sieve to 0.045-0.15mm, with a particle size of 0.045-0.075mm accounting for 40%-60%, and a particle size of 0.075-0.15mm accounting for 20%-30%.

[0013] In step S3, the flow rate of inert gas protection is 0.5-1L / min.

[0014] In step S3, the two-stage grinding is first coarse grinding to 0.15mm with a sieve residue ≤5% using a Raymond mill, and then superfine grinding to a specific surface area of 550-650m 2 / kg using an air jet mill, with a cumulative particle size of 0.02-0.075mm accounting for ≥80%.

[0015] In step S3, 0.1%-0.3% of nano calcium carbonate is added to the total amount of admixture during superfine grinding to improve the dispersibility and early hydration activity of the admixture through mechanical chemical action.

[0016] The application discloses a mine-used ultra-high-strength shotcrete active admixture and a preparation method thereof. BRIEF DESCRIPTION OF DRAWINGS

[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present application or the prior art, the following will briefly introduce the drawings needed to be used in the embodiments or the prior art description. Obviously, the drawings in the following description are only some embodiments of the present application, and for those skilled in the art, other drawings can also be obtained without creative labor on the basis of these drawings.

[0018] Figure 1 is a step flow chart of the preparation method of the mine-used ultra-high-strength shotcrete active admixture provided by the application.

[0019] Figure 2 is a step flow chart of the first embodiment of the application.

[0020] Figure 3 is a step flow chart of the second embodiment of the application. DETAILED DESCRIPTION

[0021] The embodiments of the present application will be described in detail below, and examples of the embodiments are shown in the drawings, wherein the same or similar reference signs represent the same or similar elements or elements having the same or similar functions throughout. The embodiments described below by referring to the drawings are exemplary and are intended to explain the present application, and cannot be understood as a limitation of the present application.

[0022] Please refer to Figure 1 The application provides a mine-used ultra-high-strength shotcrete active admixture, which is prepared from raw materials with the following mass percentages: 30-45% of secondary aluminum ash, 25-40% of coal gangue, 15-25% of calcium oxide and 3-6% of a composite activator; the composite activator is a mixture of sodium sulfate, calcium fluoride and sodium aluminate, and the mass ratio of the three is (2-3):1:(0.5-1); the coal gangue is underground tunneling or washing gangue with an Al2O3 content of greater than or equal to 15% and a carbon content of less than or equal to 8%, and after pretreatment, the particle size of 0.045-0.075 mm accounts for greater than or equal to 40%.

[0023] In the embodiment, the raw material mass percentage is: secondary aluminum ash 30%-45%, coal gangue 25%-40%, calcium oxide 15%-25%, and composite activator 3%-6%. The composite activator introduces sodium aluminate (0.5-1% by weight), promotes the rapid generation of ettringite by providing additional Al3+, and solves the problem of insufficient early strength of traditional admixtures.

[0024] The application also provides a preparation method of the mine ultra-high-strength shotcrete active admixture.

[0025] Step S1: The pretreated secondary aluminum ash, coal gangue, calcium oxide, and composite activator are weighed according to the proportion, put into a ball mill, and dry mixed for 20-25 minutes, and the bulk density of the mixed powder is controlled to be 1.2-1.4 g / cm 3 ;

[0026] Step S2: The mixed powder is placed in a rotary kiln, inert gas protection is performed, the temperature is raised to 850-950 DEG C at a rate of 5 DEG C / min, and the temperature is maintained for 2-4 hours to form a product with specific activity.

[0027] Step S3: After the calcined product is cooled to below 100 DEG C, two-stage grinding is immediately performed, and the mine ultra-high-strength shotcrete active admixture is obtained.

[0028] In the embodiment, the following beneficial effects are achieved:

[0029] (1) Construction performance breakthrough: through the synergistic optimization of particle size distribution and chemical admixtures, the rebound rate of UHPC is reduced from 10%-15% to below 5%, the single roadway spraying efficiency is increased by 40%, and the material loss is reduced by 15-20 tons / 100 meters.

[0030] (2) Safety performance improvement: the 2h high-strength characteristic allows the roadway to be repaired and immediately restored to traffic, the response time of emergency roof treatment is shortened to 1 / 6 of that of traditional materials, and the risk of secondary collapse is significantly reduced.

[0031] (3) Deepening of solid waste utilization: each ton of admixture consumes 0.3-0.4 tons of coal gangue, and 80 tons of gangue can be consumed for 1000 meters of roadway spraying, reducing the occupation area of gangue pile by 0.12 mu.

[0032] (4) Significant cost advantage: compared with traditional shotcrete UHPC materials, the cost is reduced by 50%, the service life of traditional shotcrete is prolonged by 5-8 times, and the whole life cycle cost is reduced by more than 60%.

[0033] In step S1, the pretreatment of the secondary aluminum ash is to immerse the secondary aluminum ash in a 10%-15% hydrochloric acid solution for 2-4 hours, and the solid-liquid ratio is 1:5. After filtration, the secondary aluminum ash is washed with deionized water until neutral, and then dried at 105℃±5℃ until the weight is constant. After crushing, the secondary aluminum ash is sieved through a 120 mesh sieve, and the proportion of particles with a size of 0.02-0.045mm is ≥50%.

[0034] In this embodiment, after hydrochloric acid immersion, the secondary aluminum ash is sieved through a 120 mesh sieve, and the proportion of particles with a size of 0.02-0.045mm is controlled to be ≥50%. The micro-filling effect is used to reduce the water demand of the sprayed material.

[0035] In step S1, the coal gangue is high-carbon coal gangue and low-carbon coal gangue, and the carbon content of the high-carbon coal gangue is 5%-8%, and the carbon content of the low-carbon coal gangue is ≤5%.

[0036] In step S1, the classification pretreatment of the coal gangue is that the high-carbon coal gangue is calcined in two stages. First, it is calcined at 300-400℃ in air for 1 hour, and then heated to 600℃±20℃ for 2 hours. The low-carbon coal gangue is directly calcined at 600℃±20℃ for 2 hours. After calcination, the coal gangue is crushed and sieved to 0.045-0.15mm, and the proportion of particles with a size of 0.045-0.075mm is 40%-60%, and the proportion of particles with a size of 0.075-0.15mm is 20%-30%.

[0037] In this embodiment, after the classification pretreatment of the coal gangue, the proportion of particles with a size of 0.045-0.075mm is controlled to be 40%-60%. This gradation forms a continuous gradation with quartz sand, which can reduce the separation of aggregate during spraying.

[0038] In step S3, the flow rate of the inert gas protection is 0.5-1L / min.

[0039] In step S3, the two-stage grinding is first coarse grinding with a Raymond mill to 0.15mm with a sieve residue ≤5%, and then superfine grinding with an air mill to a specific surface area of 550-650m 2 / kg, and the cumulative proportion of particles with a size of 0.02-0.075mm is ≥80%.

[0040] In this embodiment, after coarse grinding with a Raymond mill, superfine grinding with an air mill is introduced, which is combined with mechanical-chemical modification of nano calcium carbonate, so that the proportion of particles with a size of 0.02-0.075mm is ≥80%, which significantly improves the leveling and adhesion during spraying.

[0041] In step S3, 0.1%-0.3% of nano calcium carbonate is added during superfine grinding, which improves the dispersibility and early hydration activity of the admixture through mechanical-chemical action.

[0042] In the application, the roadway spraying construction process of the mine ultra-high strength shotcrete active admixture is (1) base treatment: high-pressure wind is used to remove floating dust of the roadway surrounding rock, and loose rock stratum is pretreated by anchoring; (2) material preparation: the product after grinding, cement, quartz sand, steel fiber, rapid-setting water reducing agent, defoaming agent and water are proportionally put into a rotor-type guniting machine, and after stirring for 120-180s, they are delivered to a spray gun through a high-pressure hose; (3) layered spraying: the first layer has a thickness of 30-50mm, the second layer is sprayed after initial setting for 20-30min, the total thickness is controlled to be 50-150mm, the included angle between the spray gun and the sprayed surface is kept to be 75°-90°, and the distance is controlled to be 0.8-1.2m; (4) curing: the sprayed surface is covered with a film within 1h after spraying, and is watered for curing after 24h, and no additional curing is needed in a humid environment, meanwhile, the mine ultra-high strength shotcrete active admixture can be used for rapid repair (roof fall area filling), broken surrounding rock reinforcement, dynamic pressure roadway reinforcement and high-gas mine sealing wall spraying of the coal mine roadway, the 2h compressive strength is ≥20MPa, the 28d compressive strength is ≥120MPa, and the bonding strength with the surrounding rock is ≥2.5MPa.

[0043] In the application, the rotor-type guniting machine is used to replace the traditional piston-type equipment, the high viscosity characteristics of the UHPC are adapted, the second layer is sprayed after the first layer has a certain strength by using the initial setting characteristics of the material for 20-30min, and layer slip is avoided.

[0044] In the application, the steel fiber is selected to be 6-13mm short-cut type, the pipe blocking risk of the guniting machine is reduced, the rapid-setting water reducing agent adopts a polycarboxylic acid system and an aluminate composite system, the initial setting time is controlled to be 15-25min, the layered spraying requirement is met, the defoaming agent is selected to be an organic silicon type, air bubbles introduced in the spraying process are eliminated, and honeycomb pitted surface is avoided, the composition has three core advantages, one is low rebound rate: the rebound rate is controlled to be less than 5% by optimizing the particle size distribution and the random distribution of the steel fiber, and more than 20% of the material is saved compared with the traditional guniting; two is rapid hardening: the 2h compressive strength is ≥20MPa, the certain surrounding rock pressure can be immediately borne, and the time efficiency requirement of the emergency repair is solved; three is high bonding: the bonding strength with the roadway surrounding rock is ≥2.5MPa, and the interlayer peeling caused by the mine pressure is avoided.

[0045] Please refer to Figures 2-3 In the application, two embodiments are also provided, as follows:

[0046] The first embodiment is as follows:

[0047] Step S1: accurately take the secondary aluminum ash 35%, coal gangue 32%, calcium oxide 25%, and composite activator 8% according to the proportion, put them into the ball mill, and control the sodium sulfate:calcium fluoride:sodium aluminate = 2:1:0.5, start the ball mill for dry mixing, set the dry mixing time to 22 minutes, and control the bulk density of the mixed powder to be 1.3 g / cm 3 ;

[0048] Step S2: place the mixed powder in a rotary kiln, introduce nitrogen as an inert gas into the rotary kiln for protection, slowly increase the temperature to 900℃ at a rate of 5℃ / min, and keep the temperature at this value for 3 hours for calcination, forming a product with specific activity;

[0049] Step S3: cool the calcined product to below 100℃, immediately perform two-stage grinding, use an air jet mill for grinding operation, and according to the proportion, add 0.2% of nano calcium carbonate, control the specific surface area of the ground product to be 600 m 2 / kg, and finally obtain a mine ultra-high strength shotcrete active admixture;

[0050] Step S4: put 30 parts of the mine ultra-high strength shotcrete active admixture, 45 parts of cement, 90 parts of quartz sand, 10 parts of steel fiber, 5 parts of rapid-setting water reducing agent, 0.3 parts of defoaming agent, and 22 parts of water into a rotor-type guniting machine according to the proportion, stir for 150 s, mix the components evenly, and form a high-strength shotcrete ready-mixed concrete with good fluidity and workability.

[0051] Second embodiment:

[0052] Step S1: accurately take the secondary aluminum ash 40%, coal gangue 30%, calcium oxide 22%, and composite activator 8% according to the proportion, put them into the ball mill, and control the sodium sulfate:calcium fluoride:sodium aluminate = 3:1:1, start the ball mill for dry mixing, set the dry mixing time to 20 minutes, and control the bulk density of the mixed powder to be 1.2 g / cm 3 ;

[0053] Step S2: place the mixed powder in a rotary kiln, introduce nitrogen as an inert gas into the rotary kiln for protection, slowly increase the temperature to 950℃ at a rate of 5℃ / min, and keep the temperature at this value for 2.5 hours for calcination, forming a product with specific activity;

[0054] Step S3: cool the calcined product to below 100℃, immediately perform two-stage grinding, use an air jet mill for grinding operation, and according to the proportion, add 0.3% of nano calcium carbonate, control the specific surface area of the ground product to be 580 m 2 / kg, and finally obtain a mine ultra-high strength shotcrete active admixture;

[0055] Step S4: 35 parts of the active admixture of the mine ultra-high strength shotcrete, 48 parts of cement, 85 parts of quartz sand, 9 parts of steel fiber, 4.5 parts of the rapid setting type water reducing agent, 0.2 parts of the defoaming agent and 21 parts of water are proportionally put into the rotor type shotcrete machine and stirred for 120s, so that the components are fully mixed and uniformly distributed, and the high strength shotcrete ready concrete with good fluidity and working performance is formed.

[0056] In the present application, the initial spread of the high strength shotcrete ready concrete is 650-750mm, the 2h spread loss of the high strength shotcrete ready concrete is ≤50mm, and the rebound rate of the high strength shotcrete ready concrete is ≤5%.

[0057] In the present application, a comparative example is also provided as follows:

[0058] The commercially available UHPC material for spraying (without coal gangue admixture) is used:

[0059] (1) 2h compressive strength 15MPa, rebound rate 8.5%, bonding strength 1.8MPa;

[0060] (2) The material cost is 2.1 times of that of Example 1, and the spraying cost of 1000 tunnels increases by 450,000 yuan.

[0061] In the present application, through the synergistic innovation of material formula and construction process, the efficient utilization of high-aluminum solid waste and coal gangue solid waste in UHPC for spraying in tunnels is realized for the first time, and the characteristics of low rebound rate, fast hardening and high bonding provide a new solution for the rapid repair and safety support of coal mine tunnels.

[0062] The above disclosure is only a preferred embodiment of the present application, and of course cannot limit the scope of the rights of the present application. Those skilled in the art can understand that the above-mentioned embodiment is implemented by all or part of the process, and the equivalent changes made according to the claims of the present application still belong to the scope covered by the present application.

Claims

1. An active admixture for ultra-high strength shotcrete used in mining, characterized in that, It is prepared from the following raw materials by mass percentage: including 30%–45% secondary aluminum ash, 25%–40% coal gangue, 15%–25% calcium oxide, and 3%–6% composite activator; the composite activator is a mixture of sodium sulfate, calcium fluoride, and sodium aluminate, with a mass ratio of (2–3):1:(0.5–1); the coal gangue is underground tunneling or washing gangue with an Al2O3 content ≥15% and a carbon content ≤8%, and after pretreatment, the proportion of 0.045–0.075 mm particles is ≥40%.

2. A method for preparing an active admixture for ultra-high strength shotcrete used in mining, comprising preparing the active admixture for ultra-high strength shotcrete used in mining as described in claim 1, characterized in that, Includes the following steps: Step S1: Weigh the pretreated secondary aluminum ash, coal gangue, calcium oxide, and composite activator according to the specified proportions, and dry mix them in a ball mill for 20-25 minutes, controlling the bulk density of the mixed powder to be 1.2-1.4 g / cm³. 3 ; Step S2: Place the mixed powder in a rotary kiln, introduce inert gas for protection, heat to 850℃-950℃ at 5℃ / min, hold for 2-4 hours to form a product with specific activity; Step S3: After the calcined product is cooled to below 100°C by air, it is immediately subjected to two-stage grinding to obtain an active admixture for ultra-high strength shotcrete in mining.

3. The method for preparing active admixtures for ultra-high strength shotcrete in mining as described in claim 2, characterized in that, In step S1, the pretreatment of secondary aluminum ash involves soaking the secondary aluminum ash in a 10%-15% hydrochloric acid solution for 2-4 hours with a solid-liquid ratio of 1:5, filtering, washing with deionized water until neutral, drying at 105℃±5℃ to constant weight, crushing, and passing through a 120-mesh sieve, wherein the proportion of 0.02-0.045mm particles is ≥50%.

4. The method for preparing active admixtures for ultra-high strength shotcrete in mining as described in claim 3, characterized in that, In step S1, the coal gangue is high-carbon coal gangue and low-carbon coal gangue, and the carbon content of high-carbon coal gangue is 5%-8%, while the carbon content of low-carbon coal gangue is ≤5%.

5. The method for preparing active admixtures for ultra-high strength shotcrete in mining as described in claim 4, characterized in that, In step S1, the pretreatment of coal gangue involves a two-stage calcination process for high-carbon coal gangue: first, calcination at 300-400℃ in air for 1 hour, followed by calcination at 600℃±20℃ for 2 hours; for low-carbon coal gangue, calcination is performed directly at 600℃±20℃ for 2 hours. After calcination, the gangue is crushed and screened to a particle size of 0.045-0.15mm, with 40%-60% of the particles being 0.045-0.075mm and 20%-30% being 0.075-0.15mm.

6. The method for preparing active admixtures for ultra-high strength shotcrete in mining as described in claim 5, characterized in that, In step S3, the flow rate of the inert gas protection is 0.5-1 L / min.

7. The method for preparing active admixtures for ultra-high strength shotcrete in mining as described in claim 6, characterized in that, In step S3, the two-stage grinding process involves first using a Raymond mill for coarse grinding until the residue on a 0.15mm sieve is ≤5%, and then using an air jet mill for ultrafine grinding until the specific surface area is 550-650m². 2 / kg, of which particles of 0.02-0.075mm account for ≥80% cumulatively.

8. The method for preparing active admixtures for ultra-high strength shotcrete in mining as described in claim 7, characterized in that, In step S3, 0.1%-0.3% of nano-calcium carbonate is incorporated into the ultrafine grinding process to improve the dispersibility and early hydration activity of the admixture through mechanochemical action.

Citation Information

Cited By

  • Early-strength low-temperature grouting material for rock stratum based on coal gangue activation and preparation method of early-strength low-temperature grouting material

    CN122102632A

  • Rock stratum early-strength low-temperature grouting material based on coal gangue activation and preparation method thereof

    CN122102632B